SISTEM INFORMASI BANTUAN PADA DINAS SOSIALPEMERINTAHAN KOTA DEPOK BERBASIS WEBSITE - Valencia Augustine (2023)
Technology is the application of knowledge, inventions, skills and processes to create useful products or services. One of the Depok city government agencies responsible for social responsibility is the Social Service. Its social services include social rehabilitation, which includes planning, implementing, evaluating, and reporting on the social rehabilitation of persons with disabilities. Due to the short time span of social assistance, the information received is often inaccurate. In addition, a large number of residents use fake identities to obtain social assistance. It is not uncommon for people in the city of Depok with incomes above the average to apply for assistance. Based on these things, the author has made it easier to collect data on citizens who apply for social assistance. The author uses the waterfall method with the PIECES method for problem identification, framework, PHP Native MySQL database, and black box testing